Physical Education 1: A Worktext for the Tertiary Level - Jose, Eviza A.; Lacerna, Evelyn B.; Mercado, Corazon R.; Pesimo, Josie M.; Piores, Victor F. (Valenzuela City, 2007)
A comprehensive worktext designed for college-level physical education, covering fundamental concepts, activities, and assessments to promote physical fitness and well-being among students.
Keywords: Phyiscal Fitness; Rhytmic activtiies